2007
DOI: 10.1037/0278-6133.26.2.192
|View full text |Cite
|
Sign up to set email alerts
|

Personal meaning of human papillomavirus and pap test results in adolescent and young adult women.

Abstract: Objective: As new cervical cancer screening recommendations are adopted, more adolescents may learn they are infected with human papillomavirus (HPV). The objective of this study was to explore personal meaning of HPV and Pap test results in adolescent and young adult women. Design: The authors recruited sexually active 14-to 21-year-old adolescent girls from an urban teen health center. Participants underwent HPV and Pap testing at baseline and returned 2 weeks later to receive test results and to be intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
1
7

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(106 citation statements)
references
References 40 publications
3
73
1
7
Order By: Relevance
“…In preliminary studies of both adults and adolescents, HPV testing has been associated with anxiety, distress, perceived stigma, and fear of further testing and treatment procedures. (13,15,16,25) These types of responses may adversely impact adolescent decisions about future STI screening and follow-up. (26,27) Our previous work has demonstrated that cognitive understanding of HPV infection and Pap tests is a key factor in predicting psychosocial and behavioral responses to HPV infection and abnormal Pap tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In preliminary studies of both adults and adolescents, HPV testing has been associated with anxiety, distress, perceived stigma, and fear of further testing and treatment procedures. (13,15,16,25) These types of responses may adversely impact adolescent decisions about future STI screening and follow-up. (26,27) Our previous work has demonstrated that cognitive understanding of HPV infection and Pap tests is a key factor in predicting psychosocial and behavioral responses to HPV infection and abnormal Pap tests.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that these types of negative responses could decrease follow-up for diagnostic or treatment procedures. (13,(15)(16)(17)(18) Education may prevent or alleviate psychosocial distress by addressing women's concerns about HPV. (19) Finally, HPV vaccines have been developed that target the HPV types most commonly associated with cervical cancer, genital warts, or both.…”
Section: Introductionmentioning
confidence: 99%
“…Field notes taken during interviews were added to transcripts prior to analysis. Data were analyzed using a five-step framework analysis approach (familiarization, identification of thematic frameworks, indexing, charting, mapping/interpretation) 20,21 and employing NVivo (version 10). Following familiarization with the data, the first author generated preliminary themes.…”
Section: Methodsmentioning
confidence: 99%
“…11,30 When considering how these clinicians adapted the guidance, several general lessons emerged. In general, clinicians (20) ''The first important thing is to make sure, number one, that the person who you're prescribing for understands what PrEP is, that it's not 100% protection against getting HIV, and that we do recommend using it as part of a comprehensive HIV prevention strategy if they're using condoms and STI testing, partner communication, all the things that we're already doing and using PrEP as an added component to that.'' Counseling about need for adherence to PrEP medication…”
mentioning
confidence: 99%
“…In this way we will manage to minimize the adverse psychosocial consequences and promote positive sexual behaviour [11].…”
Section: Give True and Precise Informationmentioning
confidence: 99%